PENINGKATAN KAPASITAS MASYARAKAT DALAM MENGHADAPI RISIKO BENCANA BERBASIS GENDER - Fitri Susilowati; Lilik Siswanta (LPPM UNS, 2016)
The purposes of community service activity are: (1) raise public awareness toward disaster risk is that have potentially to damage the property of human life and life itself; (2) living in harmony with nature. The partners of this activity are a hamlet chief, youth organization (Karangtaruna), and group of women (PKK) in Patalan, Jetis, Bantul. The model of method of devotion that has been conducted are coaching and counseling, mentoring, simulations and providing mitigation equipment. Detail of activities in order to improvement community of capacity i.e. socialization, Focus Group Discussion (FGD), determine the evacuation route, develop organizational relation, Standard operating procedures (SOP), First Aid Training and Simulation. Activity of community service was very supported by Local Coping Disaster Board (BPBD) Bantul. The impact of activities are: (1) increasing the awareness, knowledge, skills and capacity for disaster risk management, (2) increasing the role of women in disaster mitigation, (3) the increasing of community preparedness in order to coping disaster risk, (4) Developing of SOP document , Relationship institutional, Voluntary team), (5) opening of access for cooperation with the administering agency disaster Management District level, i.e BPBD Bantul, (6) Realization of improvement of skill community related with of disaster mitigation, (7) Establishment of module activities, (8) the establishment of the voluntary team hamlet, (9) realization of village disaster preparedness.Keywords : Gender, risk, disaster, capacity, mitigation